Distillation - Innovative Applications and Modeling 2017
DOI: 10.5772/66774
|View full text |Cite
|
Sign up to set email alerts
|

Distillation Techniques in the Fruit Spirits Production

Abstract: During the distillation of the fermented fruit mash or juice, ethanol and water are the carriers of a huge number of the other volatile aroma compounds. Unique and distinctive lavour of the inal spirits depends on their quantity and quality. Fruit spirits have higher concentration of almost all types of volatile compounds with comparing to other types of distilled spirits. The art of distillation run is to obtain the best balance between congeners present. Two diferent types of distillation equipment are used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(115 citation statements)
references
References 43 publications
3
112
0
Order By: Relevance
“…Surprisingly, ethyl acetate is not detected in triple distillation. In small quantities, Ethyl acetate gives a fruit‐like odor however in large amount gives glue‐like sharp odor to the distillated (Spaho, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, ethyl acetate is not detected in triple distillation. In small quantities, Ethyl acetate gives a fruit‐like odor however in large amount gives glue‐like sharp odor to the distillated (Spaho, ).…”
Section: Resultsmentioning
confidence: 99%
“…In high concentration (over 120 g/hl p.a), it gives pungent odor, however in low concentration, it gives hazelnut, cherry, and overripe apple notes. It is reported that the content of acetaldehyde depends on fermentation process and manner of distillation cut (Spaho, ). Anise aldehyde and anisyl acetone are determined as aniseed‐based carbonyl compounds in the fractions.…”
Section: Resultsmentioning
confidence: 99%
“…High levels of ethyl carbamate (ranging between 0.01 and 12 mg/L) can be found in distilled spirits, mainly in stone fruit spirits [20], depending on their origin [27]. As more than 80% of ethyl carbamate is formed, the next 4 h after distillation ends, it is important to avoid its accumulation by applying few measures: chemical elimination of cyanide in fermented juices and after distillation and the replacing of copper condensers with stainless steel ones or proper separation of heads, as HCN has a low boiling point-25.7°C [28].…”
Section: Quality Parameters Of Distilled Beveragesmentioning
confidence: 99%
“…Despite common laboratory methods used to test de-fermented marc quality, recent studies applied advanced methods. The quality of raw material subjected to fermentation, yeast specie and the inoculum amount, type and hygiene of the vessels [65], temperature and duration of the process are parameters intensively tested in the past years [20,26,28,66,67]. Yeast species used in fermentation have an important role in defining the final bouquet of the beverage, a gas-chromatography analysis proved [68].…”
Section: Biomarkers Formed During Fermentation Processmentioning
confidence: 99%
“…Arrieta-Garay et al (6) and Balcerek et al (35) reported a higher concentration of acetaldehyde in distillates obtained by rectification column. These differences in the published results are supported by the content of acetaldehyde corresponding more to the head/heart cut than the distillation equipment used (36).…”
Section: Fermentative Aroma Compounds Distillation Technique and Ageingmentioning
confidence: 92%